(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
The progressive education movement in Germany was a reflection to those phenomena that attempted societal, cultural and philosophical renewal, and thus challenged traditional education for about four decades. It included those educational phenomena that were aimed directly at the changing education in the various aspects of societal and cultural life. Its language and theory have vanished, but the problems it attempted to solve are still hot in the 21st century.